Analisis Keluhan Nabi Habakuk Dalam Penderitaan (Habakuk 1:2-4) - Trivena Br Nadeak; Sisga Desriman Zebua; Asima Putri Handayani Nababan; Yubilate Christwell Zebua; Herdiana Boru Hombing (Jurnal Pendidikan Agama dan Teologi, 2023)
The prophet Habakkuk was a prophet who lived in very similar times and is still relevant today, and he struggled with the commonplace question that believers should ask “why did God allow curses to happen?”  Habakkuk lived in a time of suffering, oppression of injustice, crime, hatred and division was rampant, the wicked surrounded the righteous.  The method used in this study is a qualitative method based on literature studies, namely by using data collection methods, using reliable and accurate sources such as journals, books, and the Bible.  Difficult circumstances and a sense of injustice surrounded his prophetic vocation, but in fact this did not prevent the prophet Habakkuk from fulfilling the Mission God gave him.  When the prophet Habakkuk asked God for help, he did not know of any evidence of an answer from God to his cry.  He only saw that God only seemed to be silent and did not want to answer his call, but he was sure that God would answer his prayer.  Habakkuk's sense of certainty comes from his living faith in the midst of suffering.  Habakkuk's poem provides an example for today's people to have a long-suffering, steadfast attitude, and think positively in facing difficult times.